Detection of Thalidomide Embryotoxicity by In Vitro Embryotoxicity Testing Based on Human iPS Cells - Nobuo Aikawa; Atsushi Kunisato; Kenji Nagao; Hideaki Kusaka; Katsumi Takaba; Kinya Ohgami (Elsevier, 2014)
The mouse embryonic stem cell test (mEST) is used to assess the embryotoxicity of drug candidates by evaluating the effects on the cardiac differentiation of stem cells. However, thalidomide embryotoxicity has not yet been reported using the mEST. To detect the effects of thalidomide, we used human induced pluripotent stem cells (hiPSCs) instead of mouse embryonic stem cells, and assessed three endpoints: the inhibition of cardiac differentiation, the cytotoxicity to hiPSCs, and the cytotoxicity to human dermal fibroblasts, according to the mEST. From these data (IC50 values), the embryotoxicity was classified into one of three different classes based on the mEST and our criteria. Valproate was used as a positive control and ascorbic acid was used as a negative control, and their effects were assessed. Similar to valproate, thalidomide was classified as a Class 2 agent, with weak embryotoxicity, by the mEST criteria, and was classified as Category 3 embryotoxic based on our criteria. Ascorbic acid was classified as a Class 1 / Category 1, non-embryotoxic agent, based on both criteria. Thalidomide embryotoxicity was detected in the embryonic stem cell test based on hiPSCs. This test system is thus considered to have a much greater predictive ability than the mEST. Keywords:: embryonic stem cell test, iPS cell, thalidomide, embryotoxicity, teratogenicity